Complete and incomplete intestinal metaplasia at the oesophagogastric junction: prevalences and associations with endoscopic erosive oesophagitis and gastritis. Issue 5 (1st November 1999) - Voutilainen, M; Färkkilä, M; Juhola, M; Mecklin, J-P; Sipponen, P
Abstract : BACKGROUND/AIMS: Intestinal metaplasia (IM) is a common finding at the oesophagogastric junction, but the aetiopathogenesis of the different IM subtypes—that is, incomplete IM (specialised columnar epithelium, SCE) and complete IM— and their associations with gastro-oesophageal reflux disease and Helicobacter pylori gastritis are unclear. METHODS: 1058 consecutive dyspeptic patients undergoing gastroscopy were enrolled. The gastric, oesophagogastric junctional, and oesophageal biopsy specimens obtained were stained with haematoxylin and eosin, alcian blue (pH 2.5)-periodic acid Schiff, and modified Giemsa. RESULTS: Complete junctional IM was detected in 196 (19%) of the 1058 subjects, and in 134 (13%) was the sole IM subtype. Incomplete junctional IM (SCE) was detected in 101 (10%) subjects, of whom 62 (61%) also had the complete IM subtype. Of patients with normal gastric histology (n = 426), 6% had complete IM and 7% junctional SCE. The prevalence of both types of IM increased with age in patients with either normal gastric histology or chronic gastritis (n = 611). Epithelial dysplasia was not detected in any patients with junctional IM. In multivariate analysis, independent risk factors for incomplete junctional IM were age (odds ratio (OR) 1.3 per decade, 95% confidence interval (CI) 1.2 to 1.6), endoscopic erosive oesophagitis (OR 1.9, 95% CI 1.1 to 3.2), and chronic cardia inflammation (OR 2.9, 95% CI 1.3 to 6.2), but not gastric H pylori infection (OR 1.0, 95% CI 0.6 to 1.7). In univariate analysis, junctional incomplete IM was not associated with cardia H pylori infection. Independent risk factors for "pure" complete junctional IM (n = 134) were age (OR 1.2 per decade, 95% CI 1.0 to 1.4), antral predominant non-atrophic gastritis (OR 2.6, 95% CI 1.3 to 5.2), antral predominant atrophic gastritis (OR 2.1, 95% CI 1.1 to 5.2), and multifocal atrophic gastritis (OR 7.1, 95% CI 2.5 to 19.8). In univariate analysis, junctional complete IM was strongly associated with chronic cardia inflammation and cardia H pylori infection (p<0.001). CONCLUSIONS: Both complete and incomplete junctional IM are independent acquired lesions that increase in prevalence with age. Although IM subtypes often occur simultaneously, they show remarkable differences in their associations with gastritis and erosive oesophagitis: junctional complete IM is a manifestation of multifocal atrophic gastritis, while the incomplete form (SCE) may result from carditis and gastro-oesophageal reflux disease. The frequency of dysplasia in intestinal metaplasia at the oesophagogastric junction appears to be low.